FUNGAL INFECTIONS OF THE EAR IN IMMUNOCOMPROMISED HOST: A REVIEW - Borlingegowda Viswanatha; Khaja Naseeruddin (Mediterranean Journal of Hematology and Infectious Diseases)
Otomycosis is a fungal infection of the external ear; middle ear and open mastoid cavity. Meyer first described the fungal infection of the external ear canal in 1884.External ear canal has the ideal warm humid environment for the proliferation of fungus. Although this disease is rarely life threatening, it can presents a challenging and frustrating situation for the otologist and patients due to long term treatment and high rate of recurrence .Otomycosis is seen more frequently in immunocompromised patients as compared to immunocompetent persons. Recurrence rates are high in immunocompromised patients and they need longer duration treatment and complications are more frequent in immunocompromised patients. In the recent years; opportunistic fungal infections are gaining greater importance in human medicine as a result of possibly huge number of immunocompromised patients. In immunocompromised patients, it is important that the treatment of otomycosis be vigorous, to minimize complications such as hearing loss, tympanic membrane perforations and invasive temporal bone infection . Fungal cultures are essential to confirm the diagnosis. Hematological investigations play a very important role in confirming the diagnosis and immunity status of the patients. In diabetic patients with otomycosis, along with antifungal therapy blood sugar levels should be controlled with medical therapy to prevent complications.